The Manners Of Cognitive Processin Translating English Phrasal Verbs Into Indonesian - Fitri Ervina Tarigan, Anni Holila Pulungan, Rahmad Husein (Pusdikra Publishing, 2021)
This study dealt with the cognitive process of students in translating English Phrasal Verbs into Indonesian by using the think-aloud protocol (TAP) technique and introspective interview. The objectives of the study was1) to elaboratethe manner of cognitive processes occurring in translating English Phrasal Verbs into Indonesian . This research was conducted by descriptive qualitative design. The source of data was the bilingual students, they were sixth semester students of English Education Program at State University of Medan. The source of data were taken by using Snowballing Technique. The data consisted of the transcription of audio recorded observation of think-aloud protocols (TAP), and the transcription of interview. The findings showed that there are six behaviors available during the process of translation done by the students, namely 1) reading the text, 2) alternating between the SL and the TL 3) monitoring the proposed translation, 4) consulting the dictionary 5) paraphrasing, and 6) translation. The cognitive processes occur when the subjects 1) read the text, either they read the whole SL or segment by segment, 2) kept repeating the term (the lexical) which indicates hesitation, questioning, and remembering the real meaning 3) were not able to make decision for an equivalent, 4) did not understand the meaning of verbs and consult the dictionary, 6) tried to clarify a concept and reformulate a proposed translation by paraphrase, and 7) wrote down a translation and express it orally.